Analysis of process of emulsions transport in hydrophilic/oleophilic granular porous media driven by capillary force - Shtyka, Olga; Przybysz, Łukasz; Błaszczyk, Mariola; Sęk, Jerzy P. (Technical Sciences, 2018)
The research focuses on the issues concerning a process of multiphase liquids transport in granular porous media driven by the capillary pressure. The current publication is meant to introduce the results of experimental research conducted to evaluate the kinetics of the imbibition and emulsions behavior inside the porous structures. Moreover, the influence of the dispersed phase concentration and granular media structure on the mentioned process was considered. The medium imbibition with emulsifier-stabilized emulsions composed of oil as the dispersed phase in concentrations of 10 vol%, 30 vol%, and 50 vol%, was investigated. The porous media consisted of oleophilic/hydrophilic beads with a fraction of 200–300 and 600–800 μm. The experimental results provided that the emulsions imbibition in such media depended stronger on its structure compare to single-phase liquids. The increase of the dispersed phase concentration caused an insignificant mass decreasing of the imbibed emulsions and height of its penetration in a sorptive medium. The concentrations of the imbibed dispersions exceeded their initial values, but reduced with permeants front raise in the granular structures that can be defined as the influential factor for wicking process kinetics.